Intestinal mucosa structure of broiler chickens infected experimentally with Eimeria tenella and treated with essential oil of oregano - Silva,Maria Aparecida da (2009)
In the first trial a total of 250 day-old male chicks were distributed into five treatments and given the following diets: a diet with growth promoter; a diet without added growth promoter; a diet added with avilamycin only; diet supplemented with 0.5g of oregano oil kg diet-1; 1.0g of oregano oil kg diet-1. In other trial a total of 288 day-old chicks was used and distributed into four treatments, which were given the following diets: a diet with anticoccidial agent; a diet without anticoccidial agent; a diet supplemented with 0.5g of oregano oil kg diet-1; a 1.0g of oregano oil kg diet-1. In the first trial the nonmedicated group had the highest crypt depth which differs from chickens fed with growth promoter or with 0.5 and 1.0g of oregano oil kg diet-1. The broilers fed with positive control (antibiotic and anticoccidial) had the highest villous: crypt ratio compared with the negative control that had the lowest villous:crypt ratio and the highest oocyst excretion in litter (P<0.05) In the second trial it was observed that broilers fed with non anticoccidial agent had the highest cecal lamina propria thickeness which differ from chickens fed with anticoccidial agent in diet or supplemented with 1.0 of oregano oil kg diet-1 (P<0.05).